Splenic hydatidosis with abdominal pain – a rare presentation in a developing nation - Akhtar, Kafil; Alam, Saquib; Rab, Atia Zaka-ur; Sherwani, Rana K (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Introduction. Primary extrahepatic hydatid cysts are rare, and primary splenic hydatid cysts even rarer. Splenic hydatidosis constitutes 2% to 3.5% of all hydatid cysts. Aim. To present a case report of splenic hydatidosis with abdominal pain. Description of the case. We report here a case of isolated splenic hydatid cysts in a 23 year old female, who presented with dull dragging pain in the left hypochondrium. Diagnosis was made on computed tomography imaging of the abdomen and microscopic examination of the laminated hydatid cyst wall and supplemented with positive enzyme linked immunosorbent assay for hydatid antibodies. Conclusion. The incidence of splenic involvement by hydatid cysts is very low. Man is an accidental intermediate host, as entry of the larval forms into humans represents an end stage in its life cycle. Until recently the gold standard treatment for splenic hydatidosis was splenectomy, as medical therapy seems to be ineffective. However, the last two decades have shown a tendency towards splenic conservative surgery in suitable cases, to reduce opportunistic post splenectomy infection.
Keywords: abdominal pain; histopathology; hydatidosis; spleen